Corneal confocal microscopy in patients with distal symmetric polyneuropathy compared to controls - Pupe, Camila; Dieckmann, Gabriela; Dornas, Ricardo; Nascimento, Osvaldo (Arquivos de Neuro-Psiquiatria, 2022)
Background Diabetic neuropathy (DN) is a very common clinical condition throughout the world. The diagnostic tests currently recommended have low sensitivity, such as electromyography, or are invasive, such as skin biopsy. New techniques have been developed to identify the early involvement of the peripheral nerve. With the advent of corneal confocal microscopy (CCM), a reduction in corneal innervation in patients with DN has been observed.Objective To compare, through CCM, diabetic patients with symptomatic distal symmetric polyneuropathy (DSP) and controls.Methods In the present study, through CCM, we compared the morphological changes in the sub-basal epithelial corneal plexus of 35 diabetic patients with symptomatic DSP with 55 controls. Moreover, we sought to determine a pattern of change regarding the severity stages of DSP, comparing the clinical, laboratory, and nerve-conduction (NC) variables.Results Differences between the control and diabetic groups were observed for the following variables, respectively: age (44.9 ± 13.24 years versus 57.02 ± 10.4 years; p < 0.001); fiber density (29.7 ± 10.2 versus 16.6 ± 10.2; p < 0.001); number of fibers (4.76 ± 1.30 versus 3.14 ± 1.63; p < 0.001); number of Langerhans cells (4.64 ± 8.05 versus 7.49 ± 10.3; p = 0.035); tortuosity (p < 0.05); and thickness (p < 0.05). Furthermore, inverse relationships were found regarding fiber density and age (p < 0.01) and fiber density and the severity of the disease (p < 0.05). A positive relationship between the conduction velocity of the fibular nerve and fiber density (p < 0.05) was also observed.Conclusion Corneal confocal microscopy proved to be a fast, noninvasive and reproducible method for the diagnosis, staging, and monitoring of diabetic DSP.
Keywords: Diabetes Mellitus; Peripheral Nervous System Diseases; Confocal Microscopy